Regulatory landscape of accelerated approval pathways for medical devices in the United States and the European Union - Tanvi Gupte; Tushar Nitave; Tushar Nitave; Jogarao Gobburu (Frontiers in Medical Technology)
The landscape of medical device regulation is rapidly evolving, driven by innovations and the need to bring these technologies to patients more efficiently. This review provides a comprehensive analysis of the accelerated access pathways for medical devices in the United States (US) and the European Union (EU), focusing on the Breakthrough Devices Program (BDP) in the US and the evolving regulatory framework within the EU. Analysis of Food and Drug Administration (FDA) data reveals that from 2015 to 2024, only 12.3% of the 1,041 BDP-designated devices received marketing authorization, with mean decision times of 152, 262, and 230 days for 510(k), de novo, and PMA pathways respectively—significantly faster than standard approvals for de novo (338 days) and PMA (399 days). In the EU, where no specific accelerated pathway exists, the recently implemented Medical Device Regulation and Health Technology Assessment Regulation aim to harmonize approval processes, with joint clinical assessments beginning in 2026. The analysis explores the interplay between regulatory approval, funding mechanisms, and coverage policies that collectively determine the accessibility of medical devices. The unique challenges associated with emerging technologies and the implementation of accelerated pathways are also discussed. We recommend global regulatory convergence through harmonized standards, mutual recognition agreements, and unified post-market surveillance systems to balance innovation with patient safety.